Combination therapy with GLP‐1 receptor agonists and basal insulin: a systematic review of the literature. Issue 6 (12th November 2012) - Balena, R.; Hensley, I. E.; Miller, S.; Barnett, A. H.
<x xml:space="preserve">Abstract</x> Treatment algorithms for type 2 diabetes call for intensification of therapy over time as the disease progresses and glycaemic control worsens. If diet, exercise and oral antihyperglycaemic medications (OAMs) fail to maintain glycaemic control then basal insulin is added and ultimately prandial insulin may be required. However, such an intensification strategy carries risk of increased hypoglycaemia and weight gain, both of which are associated with worse long‐term outcomes. An alternative strategy is to intensify therapy by the addition of a short‐acting glucagon‐like peptide‐1 receptor agonist (GLP‐1 RA) rather than prandial insulin. Short‐acting GLP‐1 RAs such as exenatide twice daily are particularly effective at reducing postprandial glucose while basal insulin has a greater effect on fasting glucose, providing a physiological rationale for this complementary approach. This review analyzes the latest randomized controlled clinical trials of insulin/GLP‐1 RA combination therapy and examines results from 'real‐world' use of the combinations as reported through observational and clinical practice studies. The most common finding across all types of studies was that combination therapy improved glycaemic control without weight gain or an increased risk of hypoglycaemia. Many studies reported weight loss and a reduction in insulin use when a GLP‐1 RA was added to existing insulin therapy. Overall, the relative degree of benefit to glycaemic control and weight was influenced by the insulin titration employed in conjunction with the GLP‐1 RA. The greatest glycaemic benefits were observed in studies with structured titration of insulin to glycaemic targets while the greatest weight benefits were observed in studies with a protocol‐specified focus on insulin sparing. The adverse event profile of GLP‐1 RAs in the reviewed trials was similar to that reported with GLP‐1 RAs as monotherapy or in combination with OAMs with gastrointestinal events being the most commonly reported.